WANPRESTASI PASIEN TERHADAP GENERAL CONSENT DI RUMAH SAKIT UMUM DAERAH KEMAYORAN JAKARTA PUSAT BERDASARKAN UNDANG-UNDANG NOMOR 44 TAHUN 2009 TENTANG RUMAH SAKIT - Sampurno Bayu Aji; Rineke Sara (Fakultas Hukum Universitas Borobudur, 2024)
General consent is an initial agreement in the registration process to get treatment at a regional public hospital, by being informed and understanding about the rights and obligations as a patient. For the general public who wants to use health services from regional public hospitals, can make an initial agreement or general consent. It includes an agreement on the patient's obligation to pay the total cost of care provided in accordance with the cost reference and the provisions of the regional public hospital with a guarantee orprivate. The problems in this study are how the forms of default against general consent at the Kemayoran Regional General Hospital, Central Jakarta, how the efforts made by the Kemayoran Regional General Hospital in handling default against general consent. The research method uses a normative juridical approach and is empirical in nature. The results of this study are that the patient knows that there is a general consent made by the hospital in the form of a registration form and understands the intention to carry out obligations, one of which is to pay the treatment costs properly, but in its implementation there are still those who make arrears or defaults that harm the hospital.